2011
DOI: 10.1038/bjc.2011.523
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cell proliferation is inhibited by specific modulation frequencies

Abstract: Background:There is clinical evidence that very low and safe levels of amplitude-modulated electromagnetic fields administered via an intrabuccal spoon-shaped probe may elicit therapeutic responses in patients with cancer. However, there is no known mechanism explaining the anti-proliferative effect of very low intensity electromagnetic fields.Methods:To understand the mechanism of this novel approach, hepatocellular carcinoma (HCC) cells were exposed to 27.12 MHz radiofrequency electromagnetic fields using in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
126
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(138 citation statements)
references
References 20 publications
10
126
0
2
Order By: Relevance
“…The effect might depend on both the level and time of exposure. Interestingly, an anti-tumour effect of EMF was shown for patients with advanced hepatocellular cancer [18], and the growth of hepatocellular and breast cancer cells was significantly decreased by specific modulation EMF frequencies [19]. …”
Section: Discussionmentioning
confidence: 99%
“…The effect might depend on both the level and time of exposure. Interestingly, an anti-tumour effect of EMF was shown for patients with advanced hepatocellular cancer [18], and the growth of hepatocellular and breast cancer cells was significantly decreased by specific modulation EMF frequencies [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Since the multiple voltage-gated ionic channels are concentrated in the dense cluster, multiple stochastic resonance frequencies exist there. It is possible that the 'magic' frequencies in [68][69][70] could be explained in a similar way.…”
Section: In This Casementioning
confidence: 99%
“…As recently summarized [13] Zimmermann, 2013), these studies showed that anticancer effects were achieved at specific (for the cancer cell type) modulation frequencies and demonstrated proliferative inhibition and mitotic spindle disruption following exposure to alternating electric fields [10,11]. Furthermore, bridging important aspects of apoptosis [14,15] with extremely low frequency (ELF) pulsed-gradient magnetic fields, Zhang et al [16] showed that the latter can not only induce it, but may also block the development of neovascularization required for tumour supply.…”
Section: Introductionmentioning
confidence: 99%
“…The last decade also brought a number of in vitro and in vivo studies which documented the anticancer effects of alternating electric fields [9][10][11], including low-intensity intermediate frequency (100-300 KHz) alternating electric fields, as well as amplitude-modulated electromagnetic fields (EMF) of somewhat lower frequencies (0.1 Hz to 114 KHz) [12]. As recently summarized [13] Zimmermann, 2013), these studies showed that anticancer effects were achieved at specific (for the cancer cell type) modulation frequencies and demonstrated proliferative inhibition and mitotic spindle disruption following exposure to alternating electric fields [10,11].…”
Section: Introductionmentioning
confidence: 99%